Kesalahan Penggunaan Tanda Baca Pada Teks LHO Siswa Kelas X SMA: Prespektif Fonologi (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
The importance of using the right punctuation in writing Observation Report (LHO) texts is one aspect that needs to be considered in the Indonesian language learning process at the secondary school level. This study aims to identify errors in the use of punctuation in the Observation Report (LHO) text based on a phonological perspective, and to determine the types of errors in the use of punctuation in the LHO text of class X students of SMA Muhammadiyah 1 Surakarta. The method used in this study is a qualitative descriptive method, with the technique of listening and writing, to analyze errors in the use of punctuation in the LHO of students of SMA Muhammadiyah 1 Surakarta. Based on data analysis, this study describes the existence of language errors in the phonological aspect related to the use of punctuation. From the results of this study, it can be concluded that class X students of SMA Muhammadiyah 1 Surakarta still make errors in the use of punctuation according to the correct rules when writing LHO texts. The factors that cause these errors include lack of mastery of linguistic rules, inaccuracy in writing, low motivation to write, and lack of knowledge and interest in the use of punctuation. To overcome this problem, efforts made include providing an understanding of punctuation and its proper use, and increasing the frequency of writing practice